Using of digital media and its effect on constructing the value system of Iraqi society (Field study on a sample of the audience for the city of Baghdad model) - Mustafa, Adel Abdul Razzaq; Noshi, Zeena Saad (ALBAHITH ALALAMI, 2018)
With the great development in the field of the Internet, the talk about the new media and its implications began, And its interactive services have made the future of media material sometimes participating in it and manufacturing it at other times,the public is seeking information and choosing the appropriate ones, as well as exchanging messages with the sender after what the role of the receiver is just receiving information only.This study aims to demonstrate the effects of using digital media in various forms and types to construct the value system of Iraqi society through the identification of the following aims:Identify the most popular digital media for the Iraqi public in their daily lives on the Internet.Identify the size of daily use, favorite times, devices and tools most commonly used by the public for these digital means.Statement of the purpose of the use of digital media.Identification of the positive and negative effects of using digital means in the value system of Iraqi society.The researchers used the descriptive analytical approach. The population is the users of the digital media but were read or audible or visible and of different ages and different scientific, functional and professional specialties, they were selected in the sampling method available and the final sample (300) is single. The research showed a number of results, most importantly, the most popular digital means in Iraqi society is Facebook and comes second on YouTube. The results also indicated that the most important positive effects of the use of digital media are that they have helped to search for new scientific information, to read the country’s news, to open up to other cultures, and to introduce others to our cultures, whereas, the most important negative effects of the use of digital media on the value system of society were wasting time, Increase dispute among people in opinions and learn skills and words extraneous to society, as well as encouraging the establishment of illegal relations with the opposite gender.This shows that there is a change in the value system of Iraqi society as a result of the use of these digital means.